Typology of Balinese Traditional Ornaments in Resort Hotel Buildings in Sawangan, Kuta Selatan, Bali - Putu Gede Wahyu Satya Nugraha; Made Suryanatha Prabawa (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
Referring to the Bali Provincial Regulation Number 5 of 2005 which states that building facades must pay attention to aesthetic principles and characteristics of traditional Balinese architecture. This study aims to analyze the implementation and typology of traditional Balinese ornaments on the building of a resort hotel in Sawangan, Kuta Selatan. The use of ornaments at resorts building in Sawangan is inspired and takes forms from traditional Balinese ornaments. Therefore, it is necessary to study the characteristics of building ornaments through a typological approach and the results are useful in implementing regulations and preserving Balinese cultural values ​​in essential forms, especially in resort hotel architectural design. The method used in this study is a qualitative rationalistic approach to the concept and form of ornaments associated with traditional Balinese ornaments. The results of this study indicate a typology based on the concept of ornament forms and elements that are related or take ideas from traditional Balinese ornaments.